Pelatihan dan Pendampingan Skrining Risiko Preeklampsia di Desa Dunwahan, Maluku Tenggara - Agnes Batmomolin; Rahil Metanfanuan (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Preeclampsia is one of the dangerous pregnancy complications. The exact cause of this complication is still unknown, but almost 75% of maternal deaths in the world are due to preeclampsia. The aim of this community service activity is to conduct cadre training on the dangers of preeclampsia followed by screening for the risk of preeclampsia in pregnant women in Dunwahan Village, Southeast Maluku Regency. Screening for maternal risk factors preeclampsia is carried out by combining two approaches, namely the traditional approach and an alternative approach that has been developed. Methods for implementing training and screening activities are: interviews, lectures, collaboration for pregnancy checks and medical diagnosis, demonstrations and re-demonstrations, followed by field practice. The results of the activity showed an increase in cadres' knowledge and skills, especially understanding about preeclampsia and how to screen for the risk of preeclampsia in pregnant women. The results of preeclampsia risk screening by cadres together with the service team for all pregnant women in Dunwahan Village, Southeast Maluku Regency conveyed to the village midwife and Kolser Community Health Center with the hope that they can be followed up on an ongoing basis with monitoring and evaluation to obtain healthy mothers and babies for a strong future for the nation.